The Violence of Exclusion: A Psychoanalytical Approach Toward Intersectionality, Identity, and Hegemony - Valdés, Alicia (Studies in gender and sexuality, 2023)
When one looks from a feminist and critical point of view at how the Symbolic is created through the structure of the Master's Discourse, one finds a necessary exclusion of specific signifiers and objects through which the subject can engage in processes of identification. This exclusion, far from being naturally given, results from power relations and hegemonic struggles to impose a Master Signifier that allows the subject to emerge. Following the idea that our current Hegemonic Symbolic (HS) is patriarchal, this article poses questions around the idea of a possible feminist Symbolic, the rejection of the Symbolic, and the articulation of intersectionality from a psychoanalytical approach that proposes to shift from identity politics to politics of identification. The speculative nature of this article aims at illustrating different outcomes and paradoxes while focusing on two specific legislative processes by the Spanish Ministry of Equality.